2020
DOI: 10.1002/brb3.1913
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D1 receptor in the NAc shell is involved in delayed emergence from isoflurane anesthesia in aged mice

Abstract: Background Delayed emergence after general anesthesia tends to occur in the elderly population, but the mechanism remains unclear. Apart from age‐related pharmacokinetic changes, the aging‐induced structural and functional alterations in the arousal‐promoting neural substrates should be considered. The nucleus accumbens (NAc) is a crucial arousal‐related nucleus, in which activating medium spiny neurons (MSNs) expressing dopamine D1 receptor (D1R) could facilitate the arousal from natural sleep. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The NAc participates in maintaining consciousness, and activation of the NAc potentiates the response to a general anesthetic (Ma and Leung, 2006). A previous study found that NAc-D1R in the NAc was involved in regulating the process of emergence from general anesthesia in aged mice (Zhang et al, 2020(Zhang et al, , 2021. These findings suggest that the NAc apparently regulates general anesthesia.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The NAc participates in maintaining consciousness, and activation of the NAc potentiates the response to a general anesthetic (Ma and Leung, 2006). A previous study found that NAc-D1R in the NAc was involved in regulating the process of emergence from general anesthesia in aged mice (Zhang et al, 2020(Zhang et al, , 2021. These findings suggest that the NAc apparently regulates general anesthesia.…”
Section: Discussionmentioning
confidence: 85%
“…Our above results show that VTA-DA neurons are involved in modulating the state of sevoflurane anesthesia. In our previous study, we found that D1 receptors in the NAc were involved in modulating the process of emergence from general anesthesia (Zhang et al, 2020(Zhang et al, , 2021. To investigate whether sevoflurane had an influence on the change in the level of dopamine neurotransmitters in VTA-related downstream NAc areas, we measured the dynamics of the extracellular dopamine concentrations during sevoflurane anesthesia in the mouse NAc.…”
Section: Dopamine In the Nac Is Altered By The State Of Sevoflurane Anesthesiamentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, microinjecting D1R agonist or antagonist facilitated or delayed the awakening from isoflurane anesthesia in young mice by activating or inhibiting D1Rs in the NAc shell, respectively. Nonetheless, this modulation capacity of D1Rs in the NAc shell declined in aged mice 37 . Meanwhile, downregulation of D1R expression in the NAc shell was detected in the aged brain, which was associated with delayed awakening in aged mice under isoflurane anesthesia 37 .…”
Section: The Role Of D1rs and D2rs In General Anesthesiamentioning
confidence: 99%
“…Studies about the DA levels and DA synthesis capacity are controversial, some reported DA synthesis capacity are relatively preserved in aging ( Karrer et al, 2017 ; Von Linstow et al, 2017 ), but Norrara et al, 2018 reported a significant decrease in the tyrosine hydroxylase immunoreactivity across nucleus accumbens in aged animals ( Norrara et al, 2018 ). The expression of D1-like dopamine receptors is reduced in the hippocampus of aged rodents ( Guo et al, 2017 ; Zhang et al, 2021 ) and humans ( Karrer et al, 2017 ), whereas the expression of D2-like receptors is less or not age-dependent ( Dang et al, 2017 ; Karrer et al, 2017 ; Seaman et al, 2019 ). Interestingly, the expression of DR4, a major D2-like receptor, prominently expressed in PV-expressing interneurons ( Andersson et al, 2012b ), is preserved in the aged mouse hippocampus ( Guo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%